Molecular characterization of norovirus GII.17 detected in healthy adult, intussusception patient, and acute gastroenteritis children in Thailand - Khamrin P. (2017)
© 2016 Noroviruses (NoVs) have been recognized as a leading cause of sporadic cases and outbreaks of acute gastroenteritis in all age groups. During the surveillance of NoVs in Chiang Mai, Thailand, four cases of the novel GII.17 NoVs were sporadically detected by RT-PCR in 2014–2015. The first case of GII.17 was detected in a healthy adult who worked for a restaurant. The second case was found in a pediatric patient who admitted to the hospital with intussusception. The third and fourth cases were found in acute gastroenteritis children. Phylogenetic analysis clearly demonstrated that GII.17 NoVs detected in this study were genetically closely related with the novel GII.17 Kawasaki reference strains. These four GII.17 NoV positive specimens were also tested by two immunochromatographic test kits in order to evaluate the sensitivity for GII.17 NoV detection. The viral loads in those specimens were determined by real-time RT-PCR. The sensitivity of GII.17 NoV detection varies by individual test kits and also depending on the amount of the viruses contained in the fecal specimens. In summary, our study reported the detection of novel GII.17 NoVs in a wide range of subjects with and without diarrhea. Therefore, continued comprehensive screening and genetic molecular characterization of NoV strains circulating in this area need to be further investigated.